Diagnostische Kriterien in der MR-Neurographie - Bäumer, Philipp (Der Radiologe, 2017)
Peripheral neuropathies are frequent and can mostly be correctly diagnosed by clinical examination and electrophysiology; however, diagnostically difficult cases are sometimes encountered especially with respect to precise localization of nerve lesions. Imaging of the peripheral nervous system has been shown to provide additional useful diagnostic information. In addition to the more widely available nerve sonography, magnetic resonance neurography (MRN) is the method of choice in diagnostically complex cases. The most important pulse sequence is a T2-weighted fat-saturated pulse sequence with high in-plane resolution and detects increased T2-weighted signals of nerve fascicles as a highly sensitive sign for nerve lesions. Further established diagnostic criteria are nerve caliber and, less commonly used, contrast agent uptake. The spatial pattern of nerve lesions aids in the diagnostic classification of neuropathies. Functional imaging techniques, such as diffusion tensor imaging (DTI) and nerve perfusion are currently under examination with respect to the clinical potential. If all other diagnostic methods, including clinical examination, electrophysiology and nerve sonography do not arrive at an unambiguous diagnosis of a peripheral neuropathy, MRN should be used. The special value of MRN is demonstrated particularly in complex nerve lesions, such as traumatic plexopathies and in partial fascicular neuropathies and many other indications.